A Survey on Inequality-Adjusted Human Development in Africa - Simplice Asongu (African Governance and Development Institute (AGDI), 2017)
The survey puts some structure on recent empirical studies from the African Governance and Development institute (AGDI) on inclusive development published between 2016 and 2017 for the most part. The emphasis is exclusively on the inequality adjusted human development index (IHDI) because of the sparse scholarly literature on the indicator which was first published in 2010. The review provides relationships between the IHDI and inter alia: foreign aid, globalisation, information and communication technology, business dynamics and knowledge economy, software piracy, finance, health worker migration and the feasibility of common cross-country policies aimed at improving the IHDI. The survey is of policy relevance because inclusive human development is fundamental to Africa's growth agenda in the post-2015 sustainable development era.
Keywords: E60; F40; F59; D60; O55; 330; Inclusive human development; Africa